Analisis Teori Firo Dalam Relasi Persahabatan Sebagai Kajian Komunikasi Antar Pribadi - Ditha Prasanti; Retasari Dewi (Jurnal Komunikasi, 2018)
Friendship relationships are becoming increasingly important for everyone who has friends. As social beings, humans certainly have the need to socialize with their environment, so that they also make friends, and some even reach the stage of friends, husband, or wife. This kind of relationship or relationship is a study that cannot be separated from interpersonal communication. In this article, the author wants to describe one of the relevant communication theories, namely the FIRO (Fundamental Interpersonal Relationship Orientation) theory. This FIRO theory is in accordance with the phenomenon described in this paper about the importance of friendly relations in interpersonal communication. The author finds an implementation of the assumption of the FIRO theory, namely human needs which consist of the need for inclusion refer to the need to be known and interact; the need to hold control is seen in human desires that make a difference in their social environment; and affective needs refer to the need for compassion, attention, and love from friends.